Inhibitory Effects of Cinnamaldehyde Derivatives on Biofilm Formation and Virulence Factors in Vibrio Species - Olajide Sunday Faleye; Ezhaveni Sathiyamoorthi; Jin-Hyung Lee; Jintae Lee (MDPI AG, 2021)
Vibrio parahaemolyticus is considered one of the most relevant pathogenic marine bacteria with a range of virulence factors to establish food-related gastrointestinal infections in humans. Cinnamaldehyde (CNMA) and some of its derivatives have antimicrobial and antivirulence activities against several bacterial pathogens. This study examined the inhibitory effects of CNMA and its derivatives on biofilm formation and the virulence factors in Vibrio species, particularly V. parahaemolyticus. CNMA and ten of its derivatives were initially screened against V. parahaemolyticus biofilm formation, and their effects on the production of virulence factors and gene expression were studied. Among the CNMA derivatives tested, 4-nitrocinnamaldehyde, 4-chlorocinnamaldehyde, and 4-bromocinnamaldehyde displayed antibacterial and antivirulence activities, while the backbone CNMA had weak effects. The derivatives could prevent the adhesion of V. parahaemolyticus to surfaces by the dose-dependent inhibition of cell surface hydrophobicity, fimbriae production, and flagella-mediated swimming and swarming phenotypes. They also decreased the protease secretion required for virulence and indole production, which could act as an important signal molecule. The expression of QS and biofilm-related genes (aphA, cpsA, luxS, and opaR), virulence genes (fliA, tdh, and vopS), and membrane integrity genes (fadL, and nusA) were downregulated in V. parahaemolyticus by these three CNMA analogs. Interestingly, they eliminated V. parahaemolyticus and reduced the background flora from the squid surface. In addition, they exhibited similar antimicrobial and antibiofilm activities against Vibrio harveyi. This study identified CNMA derivatives as potential broad-spectrum antimicrobial agents to treat biofilm-mediated Vibrio infections and for surface disinfection in food processing facilities.